Pengembangan Usaha Akuaponik di Kolam Ikan TPQ & RTQ Raudhatul Adzkia Dalam Koto, Kabupaten Agam - Refilda Refilda; Rahmiana Zein; Hermansyah Aziz; Yefrida Yefrida; Zilfa Zilfa; Syukri Syukri; Matlal Fajri Alif; Yulizar Yusuf; Admi Admi; Raihan Hanif Aulia; Nurul Afifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The Community Service Team of the Chemistry Department has worked closely with the Taman Pendidikan Qur'an (TPQ) and Rumah Tahzhul Qur'an (RTQ) Raudhatul Adzkia Jorong Dalam Koto Nagari Koto Tangah in solving problems faced by partners. The pond catfish farming business supports smooth operational costs and has been running for over a year, but these results still need to be improved for TPQ and RTQ. This activity aims to develop a catfish farming business accompanied by an aquaponic cultivation business to increase income from TPQ and RTQ. The benefit of this activity is that the partners have an Aquaponics business which is cultivating catfish and vegetable plants in the fish pond. The Community Service Team transferred knowledge to partners, especially in cultivating aquaponic plants through entrepreneurship. The activities of the Community Service Team in helping partners are a form of the Andalas University Higher Education Tri Dharma. The method applied to support the realization of this community service program was through supervision, program socialization, and implementation of activities. The result of this activity was that partners could run an aquaponics business to increase income to meet the operational costs of education and teacher salaries.